Rentabilidad de la Empresa Ingeniería Integral y Construcción Engen S.A del periodo 2020-2021. - Pereira Figueroa, Germania Anahi (2024)
The case study focuses on the company Integral engineering and construction Engen S.A. in the city of Babahoyo, province of Los Ríos with RUC # 1291765609001, dedicated to the construction of civil engineering works related to urban pipelines, construction of conduits, presents a disability due to poor administration of income and expenses during the periods 2020-2021. The objective of the case study is to evaluate the profitability obtained in the company Integral engineering and construction Engen S.A. of the 2020-2021 period, it is essential to explore the company allowing good performance in the capacity of profits through income and expenses, implementing financial indicators (profitability, solvency, debt and structural) that will help us recognize the level of profitability, it should be emphasized that the results obtained allow us to detect the deficit that the entity has and thus give suggestions.